Growth Studies of Cucumber (Cucumis sativus L.) Varieties Plants by Bamboo (Dendrocalamus asper) Flour Organic Fertilizer - Zahanis, Zahanis; Ernita, Milda; Kardila, Evi; Herman, Welly; Resigia, Elara (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2021)
The aim of the study was to analyze the interaction between the concentration of bamboo shoots of liquid organic fertilizer and cucumber plant varieties on the growth and yield of cucumber plants. This experiment used a Completely Randomized Design (CRD) with two factors. The first factor is the type of cucumber plant varieties, Wulan F1 variety and Mercy F1 variety. The second factor is the addition of Bamboo Shoots POC which consists of 4 levels, 0, 50, 75 and 100 ml/liter of water. The parameters observed were stem length, age of first flower appearance, age of first harvest, number of planting fruit, fruit diameter, fruit length, fruit weight of crop, fruit weight per plot and per hectare. Based on the results of the experiment, it can be concluded that giving bamboo shoots POC 100 ml/liter of water can increase the growth and yield of cucumber plants reaching 47.31 tons/ha.